Accuracies of Computer versus Manual Linkages of Routine Health Records - Smith, Martha E.; Newcombe, H. B. (Methods of Information in Medicine, 1979)
Empirical tests of the application of computer record linkage methods versus the use of routine clerical searching, for bringing together various vital and ill-health records, have shown that the success rate for the computer operation was higher (98.3 versus 96.7 per cent) and the proportion of false linkages very much lower (0.1 versus 2.3 per cent). The rate at which the ill-health records were processed by the computer was approximately 14,000 per minute of central processor time, representing a cost of a half a cent apiece.Factors affecting the speed, accuracy and cost of computerized record linkage are discussed.
Keywords: Record Linkage; Cost of Linkage; Name Retrieval; Computer Searches; Manual Searches